THE EFFECT OF LOCAL BRAND CONCIOUSNESS AND NEED FOR UNIQUENESS TOWARDS EMOTIONAL VALUE AND BUYING INTENTION ON LOCAL BRANDS - Sulhaini .; Rusdan .; Sulaimiah .; Rahman Dayani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
This study aims to build a theoretical model of the influence of local brand consciousness and need for uniqueness on emotional value and willingness to buy local brands. This study develops the concept of local brand consciousness in the fashion product category that is rooted in the concept of consumer ethnocentrism. This study measures the perceptions of educated young consumers. Samples are students as the next generation who are expected to provide an overview of their preferences between local brands or global/foreign brands. This study shows that educated young consumers are local brand conscious that influence their perceptions regarding the emotional value of local brands and inspire their desire to buy local brands. However, need for uniqueness makes them negatively view local brand emotional value and affect their desire to buy a local brand. This shows that when they have a strong desire to be different, they view local brands as not providing positive emotional value. The results of this study provide an important recommendation, namely that local brand owners must increase the emotional value of their brands by understanding the needs of young consumers to appear unique and participate in increasing local brand awareness among domestic consumers especially young consumers.